2015
DOI: 10.1002/2015jg003097
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of polycyclic aromatic hydrocarbons with algae‐derived organic matter in sediment cores from a subtropical region

Abstract: The influence of algae-derived organic matter (AOM) and climate warming on the historical record of polycyclic aromatic hydrocarbons (PAHs) in the subtropical reservoir sediments was investigated. The profiles of PAH concentrations and AOM contents at the eutrophic and meso-eutrophic reservoirs are significantly elevated and show good correlations with increasing mean air temperature during the past 60 years, suggesting that increasing temperature plays a significant role in increase of algal productivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…The water phase was poured back into the separatory funnel for extraction with 50 ml of the same solvent mixture. The extract was concentrated to 2 ml under a gentle stream of nitrogen using a rotary evaporator and then analyzed by GC-MS [11]. The U.S. Environmental Protection Agency (EPA) PAH standard (16 PAHs) was used for identification [16].…”
Section: Sampling and Analysismentioning
confidence: 99%
“…The water phase was poured back into the separatory funnel for extraction with 50 ml of the same solvent mixture. The extract was concentrated to 2 ml under a gentle stream of nitrogen using a rotary evaporator and then analyzed by GC-MS [11]. The U.S. Environmental Protection Agency (EPA) PAH standard (16 PAHs) was used for identification [16].…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Aquaculture and dredging activities are forbidden in the investigated reservoirs. Detailed descriptions of the study sites are shown in the previous literature (Duan et al, 2015). In brief, ZT is a shallow, polymictic reservoir with a mesotrophic level, whereas LA is a deep and mesotrophic reservoir.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%
“…Each sliced sample was analyzed for 210 Pb and 137 Cs radiometric dating (Duan et al, 2015). Briefly, the activities of 210 Pb and 137 Cs were measured by a S-100 Multi Channel Spectrometer (Canberra, USA) with a PIPS Si detector and a GCW3022 H-P Ge coaxial detector, respectively.…”
Section: Rate Of Sedimentationmentioning
confidence: 99%
“…The monosaccharide profiles at ZT and LA show a good correlation with T 5 during the past 60 years (for ZT, galactose: T 5 , R 2 = 0.824, p < 0.01; mannose: T 5 , R 2 = 0.824, p < 0.01; fucose: T 5 , R 2 = 0.805, p < 0.01; for LA, galactose: T 5 , R 2 = 0.885, p < 0.01; mannose: T 5 , R 2 = 0.699, p < 0.01; fucose: T 5 , R 2 = 0.883, p < 0.01;), suggesting that an increase in temperature enhances the deposition of carbohydrates in sediments (Fig. 5 and weaker correlations with T 5 than carbohydrates for the sediment cores of ZT and LA (Table S5; Duan et al, 2015). The TN and TP concentrations can be used to reflect the historical inputs of nutrients in the ZT and LA reservoirs.…”
Section: Effects Of Climate Change On Primary Productivity and Carbohmentioning
confidence: 99%
“…Relationship of HI with monosaccharide compounds in the ZT, LA, and XFJ reservoirs (for LA, the sample at 8-10 cm depths and at 30-34 cm depths were excluded; for XFJ, samples below 16 cm were excluded). The HI data are cited from Duan et al (2015).…”
Section: Diagenesis Of Neutral Carbohydratesmentioning
confidence: 99%